Psychiatric Disorders Late in Life A Comprehensive Review (Springer International Publishing, 2018)
This book provides a comprehensive yet concise review of the latest information available in geriatric psychiatry. The text covers topics that include the social aspect of aging, treatment and diagnosis options unique to the elderly in need of psychiatric care, policy and ethics, and particular geriatric health concerns that may influence psychiatric considerations. This book also provides the up-to-date information from the field of geriatric psychiatry which will assist clinicians who are studying for either the American Board of Psychiatry and Neurology subspecialty examination or other professional examinations in geriatric psychiatry. Psychiatric Disorders Late in Life is the ultimate resource for practicing psychiatrists, physicians, geriatricians, and medical students concerned with the mental healthcare of the elderly.